'A legend somewhat larger than life': Karl H. von Wiegand and the trajectory of Hearstian sensationalist journalism. Issue 265 (5th July 2021) - Goldstein, Benjamin S
Abstract: This article re-evaluates the trajectory of sensationalism within twentieth-century American journalism and foreign correspondence by examining William Randolph Hearst's chief foreign correspondent, Karl H. von Wiegand (1874–1961). By following von Wiegand's activities as a journalist, celebrity, propagandist and diplomatic go-between through both world wars, it argues that post-World War I concerns over propaganda and commercial mass media's reliability impacted the typically sensational methods of foreign correspondents particularly strongly. In von Wiegand's case, his exceptionally sensational style, which became entangled in fascist propaganda throughout the 1930s and fell under an increasingly systematic ethical critique, caused his own reputation and ability to impact public opinion to weaken drastically.